1989
DOI: 10.1073/pnas.86.7.2388
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-channel blockers inhibit the action of recombinant platelet-derived growth factor in vascular smooth muscle cells.

Abstract: Human platelet-derived growth factor (PDGF) is mainly composed of two polypeptide chains (PDGF-AB). All three possible dimeric forms of PDGF-i.e., PDGF-AA, PDGF-BB and PDGF-AB-exist in nature. We have used two recombinant PDGF homodimers to determine the roles of each isoform in the activation of phosphatidylinositol turnover in vascular smooth muscle cells (VSMC) isolated from rat thoracic aorta, their mitogenic effect on VSMC, and their vasoconstrictor effect on intact strips of aortic vascular tissue. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(58 citation statements)
references
References 29 publications
8
50
0
Order By: Relevance
“…It is possible that the calcium channel blockers could interfere with the binding of the mitogens to their receptors on the cell, or that they might be uncoupling receptor activation from signal transduction pathways within the membrane, as suggested by Block et al 7 Evidence for these mechanisms comes from their studies with vascular smooth muscle cells, in which they found that calcium channel blockers not only inhibited PDGF-induced mitogenesis but also PDGF-induced vasoconstriction. They demonstrated that the three calcium channel blockers verapamil, nifedipine, and diltiazem all prevented the increases in cytosolic calcium, phosphoinositide turnover, and production of diacylglycerol induced by PDGF-BB and that the first two calcium channel blockers also prevented translocation of protein kinase C to the plasma membrane induced by PDGF-AA.…”
Section: Methodsmentioning
confidence: 95%
“…It is possible that the calcium channel blockers could interfere with the binding of the mitogens to their receptors on the cell, or that they might be uncoupling receptor activation from signal transduction pathways within the membrane, as suggested by Block et al 7 Evidence for these mechanisms comes from their studies with vascular smooth muscle cells, in which they found that calcium channel blockers not only inhibited PDGF-induced mitogenesis but also PDGF-induced vasoconstriction. They demonstrated that the three calcium channel blockers verapamil, nifedipine, and diltiazem all prevented the increases in cytosolic calcium, phosphoinositide turnover, and production of diacylglycerol induced by PDGF-BB and that the first two calcium channel blockers also prevented translocation of protein kinase C to the plasma membrane induced by PDGF-AA.…”
Section: Methodsmentioning
confidence: 95%
“…2). This rapid and protracted redistribution of PKC in response to phorbol esters has been described in a variety of cell types [24][25][26][27]30,31].…”
Section: Discussionmentioning
confidence: 99%
“…First, the increased A-chain expression may be associated with an incomplete stimulation of cell growth (34). Interestingly, a glioma-derived PDGF A-chain homodimer may be less potent than either the A-B heterodimer or the B-chain homodimer in its mitogenic activity and its ability to stimulate receptor autophosphorylation (35). Recently, a transmembrane tyrosine kinase has been isolated that efficiently binds PDGF A-chain homodimers but is structurally distinct from the PDGF B-type receptor (36).…”
Section: Discussionmentioning
confidence: 99%